Editorial - Comité Editorial, FII (1998)
Industrial Engineering in today's world, changing and debunker, near the end of the second millennium, is immersed in a series of problems resulting from technological development of the various industries that have allowed transformations in different fields of economic and social activity. The challenges facing the domestic industry has much to do with the productive sector of the country, as well as to society, institutions, customs and values ​​that have shaped the foundations on which the Industrial Engineering plans and implements production systems goods and services in the pursuit of excellence in productivity and rationality to economic and humanistic approach.